The Sistem Monitoring Kualitas Air Pada Pembudidayaan Ikan Air Tawar Menggunakan ESP 32 dan ESP 8266 - Rasyid, Muh Rafli; Nurhidayah; Fahmi Rustan, Muh (JASEE Journal of Application and Science on Electrical Engineering, 2023)
Indonesia is one of the countries that has natural resources in the form of abundant water; these geographical conditions can be utilized to support the growth and development of fish farming businesses in Indonesia; production results are very dependent on fish cultivation methods in freshwater fish, water quality is one of the most important factors in fish farming because it has an impact on fish quality and production, several parameters such as pH, temperature, and water turbidity are one of the influential factors in the success of freshwater fish farming. In this study, a system was built that could record water quality in fish ponds in real-time and monitor water conditions in fish ponds using several sensors, including a pH-4502C sensor to measure pH, a DS18B20 sensor to measure temperature, and a turbidity sensor to detect water turbidity. The test results obtained an accuracy of the reading value of 95.00% for pH, 97.33% for temperature, and 90.53% for turbidity. All data obtained by the sensor will be displayed on the website page as an interface, and the Telegram application will send and display Notifications of water conditions to cellphone cultivators.